Gas emission study of a crop residue burning machine. Issue 1 (April 2021) - Sulastri, N N; Long, J; Buser, M; Funk, P
Abstract: Crop residue burning is a common agriculture practice to eliminate post-harvest vegetative material, which hinders the seedling of the next crop. A prototype of a crop residue burning machine was developed and equipped with six LPG burners. The burners were designed as a forced-draft burner where the air was supplied by a blower/pump. While open field burning is a practical and economical practice for controlling insects, diseases, and weeds, the environmental risks of this activity are an issue. Open biomass burning is a major source of global air pollutants and has a major impact on global climate change. This study aimed to estimate the concentration of CO and NOx emitted from the combustion using this prototype. CO and NOx are important indirect greenhouse gases that affect the formation of tropospheric ozone or change the lifetime of methane. The air pollutants were measured using ECOM-EN2. The gas velocity, static pressure, and gas concentration were sampled with 1 minute's average sampling time. Gas emission study shows a high concentration of O2 in the flue gas. The recorded CO and NOx concentration exceeds the concentrations that regulated by EPA NAAQS. The average combustion efficiency of 98.0±0.3%, the highest emission factors for CO, NO, and NO2 are 57, 3.7, and 0.5 lb/acre, respectively.